Developing and evaluating the feasibility of the Mobile Intervention for Breastfeeding counseling in maternity care - Nikula, Pirkko; Kanste, Outi; Pölkki, Tarja (Finnish Journal of eHealth and eWelfare, 2024)
Despite the strong evidence of breastfeeding benefits for mothers’ and newborns’ nutrition and health, breastfeeding is not practiced according to current recommendations. Digital solutions such as the mobile applications have produced promising results to promote successful breastfeeding in maternity care. This study aimed to develop and evaluate the feasibility of a Mobile Intervention for Breastfeeding counseling (MIBFc) by collecting information on the usability, utility, and recommendations of the solution from mothers. The MIBFc was based on World Health Organization recommendations for breastfeeding. This study was a cross-sectional descriptive design that used an electronic survey to collect data from sample of 39 Finnish mothers in 2018 (n=13, Group 1) and 2019–2020 (n=26, Group 2). The data were analysed using descriptive statistical analysis, while qualitative responses were grouped into themes based on their similarities of the content. The results showed that most of the mothers (over 92%) felt that the mobile intervention was easy to use and 88% of the mothers felt that the mobile intervention’s content was adequate. Mothers’ experiences with the utility of the mobile intervention were relevant, that is, they felt that the mobile intervention supported their oral guidance (89%) and helped to breastfeed for up successfully exclusively to six months (n=7, 41%). Most of the mothers used the mobile intervention primarily during pregnancy. The mothers were satisfied with the intervention’s layout, and they recommended it to other mothers in same situation, although there were some technical problems with links. This study indicated that the feasibility of the MIBFc, including usability and utility was good, based on the mothers’ overall evaluation. Using the mobile intervention can increase mothers’ knowledge of breastfeeding and support for lactation. The study highlights a need for future evaluations of the effectiveness of MIBFc in large populations.